Engineering coupled consortia-based biosensors for diagnostic - Rongying Huang; Valeriia Kravchik; Rawan Zaatry; Mouna Habib; Naama Geva-Zatorsky; Ramez Daniel (Nature Communications)
Abstract Synthetic multicellular systems have great potential for performing complex tasks, including multi-signal detection and computation through cell-to-cell communication. However, engineering these systems is challenging, requiring precise control over the cell concentrations of distinct members and coordination of their activity. Here, we develop a bacterial consortia-based biosensor for Heme and Lactate, wherein members are coupled through a global shared quorum-sensing signal that simultaneously controls the activity of the diverse biosensing strains. The multicellular system incorporates a gene circuit that computes the minimum between each biosensor’s activity and the shared signal. We evaluate three consortia configurations: one where the shared signal is externally supplied, another directly produced via an inducible gene circuit, and a third generated through an incoherent feedforward loop (IFFL) gene circuit. Among these configurations, the IFFL system, which maintains the shared signal at low and stable levels over an extended period, demonstrates improved performance and robustness against perturbations in cell populations. Finally, we examine these coupled consortia to monitor Lactate and Heme in humanized fecal samples for diagnostics.